TikTok Influencers: How age affects popularity - Ma Yingjia (SHS Web of Conferences, 2024)
TikTok has become one of the most popular social media apps today, its user-generative nature allows anyone to upload videos onto the platform with the potential to become famous. This gives rise to TikTok influencers, and content creators with a large number of followers on TikTok. This paper offers a qualitative study on how the age of TikTok influencers affects their popularity through a literature review and TikTok content analysis. The research result reveals that younger TikTok influencers are more popular than older TikTok influencers. This difference in popularity is a result of the different nature of their video content and ways of presentation. Compared to older influencers, younger influencers tend to have greater content diversity, better technological skills to generate videos with more captivating effects and presentation style, and higher compatibility with TikTok’s user demographics. Furthermore, due to the generation gap between young and old people, the predominately young social media users tend to discriminate against older content creators on the platform, causing them to have more difficulties in gaining popularity.